Savoring disgust : the foul and the fair in aesthetics - Korsmeyer, Carolyn (New York ; Oxford : Oxford University Press, 2011)
Disgust is a strong aversion, yet paradoxically it can constitute an appreciative aesthetic response to works of art. Artistic disgust can be funny, profound, sorrowful, or gross. This book examines numerous examples of disgust as it is aroused by art and offers a set of explanations for its aesthetic appeal.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Aversion; Aesthetics